Implementasi Bagi Penyandang Disabilitas dalam Perolehan Surat Izin Mengemudi (SIM) ”D” di Polresta Denpasar - Saraswati, Cinta; Agus Kurniawan, I Gede (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Granting of Driver's Licenses (SIM) to persons with disabilities The obstacles faced by the Police in providing a driver's license (SIM) for persons with disabilities in the jurisdiction of the Denpasar Police, that in accordance with the provisions of the application for a driver's license must be completed with a Health Certificate from a doctor. This writing uses an emperical research method, namely conducting field research through interviews at the research site supported by primary and secondary data collected and processed in a qualitative descriptive manner. The Effectiveness of Driver's License (SIM) Making Services in the Administrative Unit (Satpas) of the Denpasar Police Driver's License, that the process of servicing a driver's license (SIM) "D" for persons with disabilities is carried out in accordance with the provisions of the applicable law and other related regulations and in practice the service has not been effective, due to the lack of facilities and infrastructure of practical test equipment in the form of motor vehicles specifically and their trajectories, so that there is a gap between the Das Sollen with Das Sein caused the service of a Driver's License (SIM) "D". The obstacles faced by the Police in providing driver's licenses (SIM) for people with disabilities, that with several factors as obstacles to the service of making a driver's license (SIM) "D"lack of facilities and infrastructure, there are several efforts made by the police in overcoming obstacles through the provision of special motor vehicle facilities and infrastructure for people with disabilities and their tracks.